Parent-adolescent Communication on Sexual and Reproductive Health Matters and Associated Factors among Secondary and Preparatory School Students in Robe Town, Bale zone, Southeast Ethiopia, 2017 - Mengesha Habte Niguse; Takele Melku Abulie; Teshome Alemayehu Mulusew (Journal of Public Health International, 2019)
Background Adolescents is the transition from childhood to adulthood .Which is a time of opportunity, but also one of risk. In Ethiopia, sexual and reproductive health problems of adolescents are increasing from time to time related to many parents not feeling happy to discuss sexual matters in addition to early sexual commencement among adolescents. Objective This study was intended to assess parent-adolescent communication on sexual and reproductive health matters and associated factors among secondary and preparatory school students in Robe Town, Bale Zone, South East Ethiopia, 2017. Methods Institution based cross sectional study was conducted among 394 secondary and preparatory school students in Robe town from April 10-25, 2017. Simple random sampling technique was used. Data was obtained through the use of a self administered questionnaire and supplemented by focus group discussion with parents. Data was entered using Epi Data 3.1 and analyzed by SPSS 20. Descriptive statistics and logistic regression analyses were done. Data quality was assured through careful questionnaire design, pretest and training. Results One hundred eighty six (47%) of the study participants had discussed at least two SRH issues with their parents. Grade eleven students were about nearly five times more likely discussed on sexual and reproductive matters with their parent compared with grade nine students (AOR: 4.88, 95% CI: 1.76, 13.54). Those living with relatives were 3.13 times less likely discussed as compared to those students are living with both parents (AOR: 0.32, 95%CI: (0.12, 0.80) and the odds of discussion on SRH matters is 2 times higher among females compared with their counterpart (AOR=2.02, 95% CI: 1.25, 3.26). Conclusions Communication on sexual and reproductive health matters between adolescent and parent was low. Majority of student preferred to discuss with their peers than parent. Being ashamed, parents lack of communication skill and parent knowledge on SRH issues were the major reasons mentioned by the students for not discussing about SRH matters with their parents. Therefore; comprehensive family life education needs to be initiated for the students and parents. Sexual information exchange between peers needs to be strengthened.
Keywords: parent